B lymphocytes may play a significant role in large-vessel vasculitis. (October 2012) - Alba, Marco A; Prieto-González, Sergio; Hernández-Rodríguez, Jose; Cid, Maria C
Evaluation of: Hoyer BF, Mumtaz IM, Loddenkemper K et al. Takayasu arteritis is characterised by disturbances of B cell homeostasis and responds to B cell depletion therapy with rituximab. Ann. Rheum. Dis. 71, 75–79 (2012) . The novel finding of increased number of circulating, newly differentiated, plasmablasts in Takayasu arteritis and their relationship to disease activity raises interesting questions about the role of B lymphocytes in large-vessel vasculitis. Whether this observation is relevant to the pathogenesis of vascular inflammation in Takayasu arteritis or is only a biomarker of immune activation needs to be investigated. Response of a few patients to B-cell depletion therapy supports an important role of B lymphocytes in vascular inflammation, but needs to be confirmed in clinical trials.